Pengaruh Fundamental Makro, Kinerja Keuangan, Struktur Modal, Konservatisme Akuntansi dan Struktur Kepemilikan terhadap Manajemen Laba pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Desfi Dwi Sulistyana,; Hwihanus Hwihanus, (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to determine the effect of macro fundamentals, financial performance, capital structure, accounting conservatism, and ownership structure on earnings management. This study was conducted on pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2019-2023. The number of samples used in this study was 11 companies with a purposive sampling method. Hypothesis testing in this study uses analysis on the Smart-PLS application with the Outer Model and Inner Model tests. The results of this study indicate that macro fundamentals, financial performance, capital structure, accounting conservatism, and ownership structure do not have a significant effect on earnings management. Macro fundamentals do not have a significant effect on financial performance. Macro fundamentals do not have a significant effect on capital structure. Financial performance has a significant effect on capital structure. Macro fundamentals, capital structure, and ownership structure do not have a significant effect on accounting conservatism. Financial performance has a significant effect on accounting conservatism. Macro fundamentals and financial performance do not have a significant effect on ownership structure.